A3 A PROOF-OF-CONCEPT, PHASE 2 CLINICAL TRIAL OF THE GI SAFETY OF A HYDROGEN SULFIDE-RELEASING ANTI-INFLAMMATORY DRUG (ATB-346). (15th March 2019) - Wallace, J L; Nagy, P; Feener, T; Allain, T; Ditrói, T; Vaughan, D; Muscara, M; de Nucci, G; Buret, A
Abstract: Background: Hydrogen sulfide (H2 S) is a naturally occurring mediator produced by intestinal bacteria and various eukaryotic cells, which can exert protective and analgesic effects. ATB-346 is a H2 S-releasing derivative of naproxen. In animals, ATB-346 produces negligible gastrointestinal (GI) damage and bleeding. In humans, ATB-346 was found to be much more potent and long-acting than naproxen. A human efficacy study demonstrated that ATB-346 (250 mg daily) was effective at significantly reducing pain in patients with osteoarthritis of the knee, and inhibiting systemic cyclo-oxygenase (COX) activity. COX is the targe enzyme of all NSAIDs. The aim of the present study was to determine if ATB-346 (250 mg once daily) would induce significantly less upper GI ulceration than standard dose sodium naproxen (550 mg twice daily). Aims: To determine if healthy subjects taking ATB-346 (250 mg once daily) for 14 days would develop significantly less gastroduodenal ulcers (3mm diameter with unequivocal depth) than subjects taking equi-effective anti-inflammatory doses of naproxen (550 mg twice daily). Methods: This was a double-blind, active control study. 244 healthy volunteers completed the study. Upper GI endoscopy was performed prior to and on day 14 after commencing treatment with naproxen (550 mg twice daily) or ATB-346 (250 mg once daily in the morning and placebo once daily in the evening). Whole blood thromboxane synthesis (COX activity) was measured on days 0, 7 and 14. Results: For the primary endpoint, incidence of ulcers more than 3 mm in diameter, 53 subjects (42%) taking naproxen developed at least one ulcer, while only 3 subjects (2.5%) taking ATB-346 developed at least one ulcer (p=0.00001). The two drugs produced comparable suppression of systemic COX activity. Subjects in the naproxen group developed more ulcers (an average of 4/subject) than in the ATB-346 group (an average of 1.3/subject), and a greater incidence of larger (more than 5 mm diameter) ulcers (125 vs 0, respectively; see figure). The incidence of abdominal pain, gastro-esophageal reflux and nausea were markedly lower with ATB-346 than with naproxen. Systemic COX activity was inhibited by 95% in both the ATB-346 and naproxen groups (no significant difference) and plasma H2S levels were significantly elevated in subjects treated with ATB-346 (by 50%; p=0.001). Conclusions: As in pre-clinical studies, this phase 2 clinical trial demonstrated a dramatic increase in the GI safety of ATB-346 versus one of the most widely used NSAIDs, naproxen. ATB-346 produced equivalent suppression of COX to naproxen, consistent with a previous Phase 2A trial that demonstrated significant pain relief in patients with osteoarthritis. ATB-346 appears to be an effective and much safer alternative to existing NSAIDs. Funding Agencies: CIHRAntibe Therapeutics Inc.